Stochastic controllability of systems with multiple delays in control - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
Finite-dimensional stationary dynamic control systems described by linear stochastic ordinary differential state equations with multiple point delays in control are considered. Using the notation, theorems and methods used for deterministic controllability problems for linear dynamic systems with delays in control as well as necessary and sufficient conditions for various kinds of stochastic relative controllability in a given time interval are formulated and proved.
Keywords: controllability; linear control systems; stochastic control systems; delayed controls; multiple delays